TANTANGAN MANAJERIAL DALAM MENGELOLA SUMBER DAN JENIS PEMBIAYAAN DI LEMBAGA PENDIDIKAN ISLAM - Ahmad Rifki; Hamdi Abdul Karim (STKIP Pesisir Selatan, 2026)
Islamic educational institution managers must be able to plan, organize, direct, and control funds effectively. In reality, many Islamic educational institutions still face challenges in managing their finances professionally. Financial management is a crucial aspect of the sustainability of Islamic educational institutions. This article discusses the managerial challenges faced in managing sources and types of financing in these institutions. Limited funding, which depends on internal sources such as community donations, zakat, infaq, and waqf, is a major obstacle to the development of quality education. Additionally, the lack of financial management capacity and strategic planning further complicates the process of allocating and utilizing funds effectively. This study employs a qualitative descriptive approach with literature review as the primary method. The findings indicate that strengthening managerial competencies, diversifying funding sources, and ensuring transparency in financial management are key to addressing these challenges. Therefore, collaboration between institutional leaders, the government, and the community is necessary to create a sustainable and accountable funding system to support the quality and existence of Islamic educational institutions.